Sex without words. The role of silence in anonymous sex encounters between men - Langarita Adiego, Jose Antonio (Revista de Antropología Social, 2013)
Anonymous sexual exchange between men is a common practice in various public spaces. The practice flourishes in a context defined by sexual segregation —a context in which heterosexual logic becomes hegemonic and discredits and sanctions all behaviors and desires that lay outside the man/woman binomial. As a practice it is a response that fulfills the necessity for sexual desire between men in a sexual context which is hostile towards them. This exchange, like any other social activity, is regulated by norms and consensus, of which silence is one of the most fundamental as it guarantees the maximum anonymity between participants. Thus silence becomes an indispensable tool within the sexual contract as a guarantee of secrecy while at the same time translating the dominant discourse which makes sexual difference invisible into a process of negotiation and agreement between men who participate in this kind of interaction.
Keywords: homosexuality; homophobia; ritual interaction; silence; anonymity